Pengembangan Media Pembelajaran Animasi Powerpoint Pada Pokok Bahasan Kalor - Devi Nanda Efendi; Bambang Supriadi; Lailatul Nuraini (Gravity : Jurnal Ilmiah Penelitian dan Pembelajaran Fisika, 2021)
During the Covid-19 Pandemic, teachers were be required to do online learning. Students have difficulty understanding the material provided in the online learning process, so this research aims to produce PowerPoint animation-based learning media and the effectiveness of using PowerPoint animation learning media. The research method used was Research & Development with the ADDIE research design. The research subjects consisted of 32 students of class XI MIPA 1 at SMA Negeri 1 Tanggul. From the validation provided by 2 media experts, validator and user validators (teachers), the PowerPoint animation media was declared incredibly valid with an average confirmation of 3,94. The effectiveness of PowerPoint animation media on student learning outcomes after using the PowerPoint animation learning media states that student learning outcomes increase. The increase in student learning outcomes (n-gain) was 70.69 using the average category of media effectiveness analysis. The study results stated that the PowerPoint animation learning media is feasible to apply in the learning process. Using PowerPoint animation learning media can improve student learning outcomes on heat material.